2017
DOI: 10.1515/aopf-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Maraena whitefish (Coregonus maraena) larvae reveal enhanced growth during first feeding with live Artemia nauplii

Abstract: Citation: Bochert R., Horn T., Luft P. 2017 -Maraena whitefish (Coregonus maraena) larvae reveal enhanced growth during first feeding with live Artemia nauplii -Arch. Pol. Fish. 25: 3-10.Abstract. Newly hatched Coregonus maraena (Bloch) larvae reared in aquaria were observed during two trials in 2014 and 2015 for 42 and 34 days after hatching in order to determine the on-feeding effects of different feeding strategies on growth and survival. Feeds of commercial dry feed, live Artemia nauplii, frozen rotifers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…The LF group showed highest length and body weight values during the first 20 days of the trial, and AF produced inferior results throughout the trial. Our results are similar to those of Bochert et al (2017) at 30 days, who reported enhanced growth in maraena whitefish larvae fed live Artemia nauplii at first feeding. Fish fed Artemia 6–16 dph and AF 17–42 dph displayed the highest TL and W from Day 7 to Day 42.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The LF group showed highest length and body weight values during the first 20 days of the trial, and AF produced inferior results throughout the trial. Our results are similar to those of Bochert et al (2017) at 30 days, who reported enhanced growth in maraena whitefish larvae fed live Artemia nauplii at first feeding. Fish fed Artemia 6–16 dph and AF 17–42 dph displayed the highest TL and W from Day 7 to Day 42.…”
Section: Discussionsupporting
confidence: 92%
“…Fish fed Artemia 6–16 dph and AF 17–42 dph displayed the highest TL and W from Day 7 to Day 42. With respect to growth, our results are superior to those obtained by Bochert et al (2017). Growth of fish reared at low water temperatures (Leithner & Wanzenbock, 2015) has been reported lower compared to findings of the present study.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Recent work with Maraena whitefish suggests both live and dry feed is possible (Bochert, Horn, & Luft, ; Luft & Bochert, ) but the combined effects of elevated temperatures (e.g. range of 16–20°C) and different feeding regimes have not been examined so far.…”
Section: Introductionmentioning
confidence: 99%